(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The energy usage constraint is the most critical and desired parameter in wireless sensor networks, and it is the subject of a lot of investigation. With the same motive, survey efforts have been made here, and it is focused on strategies that have been incorporated to increase energy sustainability. Apart from the above, this approach is been evaluated using Cross Layer Network for better output. The results when compared to cross layer network model outperforms good when as compared to the individual layer performance. The routers that are active in WSNs serve an significant role in terms of their position, velocity, and which cluster they are connected to. All nodes may not have the mobility to move from one place to another, for which the MEP algorithm has taken place in this research so as to identify the mobile nodes so that it has to be used for proper communication purpose in comparison with the existing models such as EQSR and ED. Each node-node distance has been evaluated for proper monitoring of the mobile nodes. Only certain nodes with adequate residual energy within themselves can generate the beaconing signal, allowing for precise propagation with minimal energy consumption. Considering the nodes which are having the mobility, the energy consumption can be reduced. It can often be reduced by only taking nodes into account with the appropriate residual energy inside the network. The states of the nodes, like Active, Sleep, Idle, as well as Dead, are also essential for interaction and must be regularly assessed in order to ensure a high PDR value. In contrast to existing protocols such as SMRC and LEACH, effective multi-hop networking is developed depending on DMRC protocol to control each and every node under either of the clusters inside the cluster head. RWS method has also taken into consideration for proper choosing of the routing path along with its estimation. Also, proper scheduling is need to assign the selected nodes for transmission for which LAB scheduling algorithm is implemented in comparison with the existing scheduling algorithms such as BOP and MeshMAC to achieve optimum system throughput. The complete work is been carried out using the NS-II simulation software.